Reducing culture medium nitrogen supply coupled with replenishing carbon nutrient simultaneously enhances the biomass and lipid production of Chlamydomonas reinhardtii - Zheng, Shiyan; Zou, Shangyun; Wang, Hongyan; Feng, Tian; Sun, Shourui; Chen, Hui; Wang, Qiang (Frontiers in Microbiology, 2022)
Chlamydomonas reinhardtii is a model strain to explore algal lipid metabolism mechanism, and exhibits great potentials in large-scale production of lipids. Completely lacking nitrogen is an efficient strategy to trigger the lipid synthesis in microalgal cells, while it always leads to the obvious reduction in the biomass. To illustrate the optimal culture substrate carbon (C) and nitrogen (N) levels to simultaneously stimulate the growth and lipid production of C. reinhardtii, cells were cultivated under altered C and N concentrations. Results showed that replenishing 6 g/L sodium acetate (NaAc) could increase 1.50 and 1.53 times biomass and lipid productivity compared with 0 g/L NaAc treatment (the control), but total lipid content slightly decreased. Reducing 75% of basic medium (TAP) N level (0 g/L NaAc + 0.09 g/L NH4Cl treatment) could promote 21.57% total lipid content in comparison with the control (containing 0.38 g/L NH4Cl), but decrease 44.45% biomass and 34.15% lipid productivity. The result of the central composite design (CCD) experiment suggested the optimum total lipid content together with higher biomass and lipid productivity could be obtained under the condition of 4.12 g/L NaAc and 0.20 g/L NH4Cl. They reached 32.14%, 1.68 g/L and 108.21 mg/L/d, and increased by 36.77%, 93.10% and 1.75 times compared with the control, respectively. It suggests moderately increasing C supply and decreasing N levels could synchronously improve the biomass and lipid content of C. reinhardtii.